Corporate-cooperative management of fisheries: A potential alternative governance structure for low value small fisheries?. (July 2015) - Coglan, Louisa; Pascoe, Sean
Abstract: While the economic and environmental benefits of fisheries management are well accepted, the costs of effective management in low value fisheries, including the research necessary to underpin such management, may be considerable relative to the total economic benefits they may generate. Co-management is often seen as a panacea in low value fisheries. Increasing fisher participation increases legitimacy of management decision in the absence of detailed scientific input. However, where only a small number of operators exist, the potential benefits of co-management are negated by the high transaction cost to the individual fishers engaging in the management process. From an economic perspective, sole ownership has been identified as the management structure which can best achieve biological and economic sustainability. Moving low value fisheries with a small number of participants to a corporate-cooperative management model may come close to achieving these sole ownership benefits, with lower transaction costs. In this paper we look at the applicability of different management models with industry involvement to low value fisheries with a small number of participants. We provide an illustration as to how a fishery could be transitioned to a corporate-cooperative management model that captures the key benefits of sole management at a low cost and is consistent with societal objectives. Highlights: Management costs may be prohibitively high in low valued small fisheries. The effectiveness of several industry driven management models is reviewed. Corporate-cooperative management appears to be a cost-effective approach. Corporate-cooperative management may also be consistent with societal objectives. How such a management system may be implemented is illustrated.